STRATEGI IMPLEMENTASI PENDEKATAN SCIENTIVIC PADA PEMBELAJARAN Al-QUR’AN HADIS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN SIKAP ILMIAH SISWA MAN DI PROVINSI ACEH - Loeziana Uce (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
This study aims to implement a scientific approach to Qur'an hadith lessons to improve students' critical thinking and scientific skills at the Public Islamic Schools (Madrasah Aliyah) in Aceh province. The research methods used were qualitative, with 13 participants, including: three supervisors and ten Qur'an hadith teachers who served in three Public Islamic Schools in Aceh province, selected purposively. Data was obtained using interviews, observations, and documentation. The result shows; (1) the strategy of implementing a scientific approach to the learning of the Qur'an hadith at the Public Islamic Schools in Aceh province begins with the preparation of a scientific-based learning implementation plan and the application of scientific steps, and (2) The application of a scientific approach has implications for improving students' critical thinking with indicators of students actively engage in learning activities, such as asking and discussing. In addition, it also has implications for improving scientific attitudes, indicated by an increase in student curiosity about learning the Qur'an hadith, respect (objective and honest), thinking critically, creative, openness in group collaboration, perseverance, and care for each other.